Texture analysis of cosmetic/pharmaceutical raw materials and formulations. (30th June 2014) - Tai, A.; Bianchini, R.; Jachowicz, J.
Synopsis Objectives The purpose of this work was to quantify textural properties of cosmetic and pharmaceutical raw materials. Methods Textural parameters such as hardness, consistency, cohesiveness, index of viscosity, stickiness and resilience were evaluated. The measurements were performed using texture analyser – a tensile metre equipped with special probes (in the form of acrylic cylinder and stainless steel sphere), which can penetrate the measured sample of a product recording the force, distance and time. The instrument simulates the action of a human finger touching the surface and probing the properties of an object. The set‐up has been previously shown to quantify the rheological/textural properties of cosmetic and pharmaceutical products such as creams, lotion and gels as well as rheological behaviour of human skin. Results and Conclusions The results include the analysis of water, glycerine and mineral oil as well as aqueous solutions of thickeners such as Acrylates/C10‐30 Alkyl Acrylate Crosspolymer (Ultrez‐20 obtained from Noveon) and carbomer. Solutions of common surfactants and complex surfactant formulations such as shampoos have also been investigated. The results, in the form plots of force as a function of time or distance, resulting from slow bidirectional probe movement (submergence and desubmergence) in the analysed fluid, were interpreted by considering buoyancy, drag and viscous drag force given by Stokes equation. The data can be used to correlate with tactile evaluations of products by trained panel evaluations.